Returnees and the Dilemmas of (Un)sustainable Return and Reintegration in Somalia - Owigo, Jacqueline (African Human Mobility Review, 2022)
Voluntary return is identified as one of the durable solutions for refugee protection under the international refugee regime. There is little research into returnees’ experiences and aspirations when they return to a home country with a high level of violent conflicts, and with severe lack of safety and stability. This article draws from semi-structured interviews held with Somali returnees who returned through the voluntary repatriation programme from Kenya. The article shows the complexity behind their return experience by advancing the discussion on return based on Carling’s (2002) aspiration and ability model. The findings show that for the majority of the returnees, return cannot be said to be sustainable as they do not return to their home and as a result are displaced in camps where they face considerable challenges finding employment, decent housing, insecurity and lack of education opportunities for their children. However, their transnational networks in Kenya also matter for their return aspirations and the majority of the returnees interviewed possess aspirations to migrate, but cannot do so due to financial costs and therefore they remain trapped in immobility. Voluntary return is identified as one of the durable solutions for refugee protection under the international refugee regime. There is little research into returnees’ experiences and aspirations when they return to a home country with a high level of violent conflicts, and with severe lack of safety and stability. This article draws from semi-structured interviews held with Somali returnees who returned through the voluntary repatriation programme from Kenya. The article shows the complexity behind their return experience by advancing the discussion on return based on Carling’s (2002) aspiration and ability model. The findings show that for the majority of the returnees, return cannot be said to be sustainable as they do not return to their home and as a result are displaced in camps where they face considerable challenges finding employment, decent housing, insecurity and lack of education opportunities for their children. However, their transnational networks in Kenya also matter for their return aspirations and the majority of the returnees interviewed possess aspirations to migrate, but cannot do so due to financial costs and therefore they remain trapped in immobility.